Effects of Plotytarya strohilacea Sieb. et Zuce Tannin on the Growth Performance, Oxidation Resistance, Intestinal Morphology and Cecal Microbial Composition of Broilers - Zhenkai Tong; Fuhong Lei; Lixuan Liu; Fei Wang; Aiwei Guo (Frontiers in Veterinary Science, 2022)
The purpose of this experiment was to study the effects of Plotytarya strohilacea Sieb. et Zuce tannin on broilers growth performance, antioxidant function, intestinal development, intestinal morphology and the cecal microbial composition. In this experiment, a total of 360 1-day-old Arbor Acres male broilers were randomly divided into 4 treatment groups, with 6 replicates in each group and 15 broilers in each replicate. The control group (Control) was fed the basal diet, and the broilers were fed a basal diet supplemented with 0 (Control), 100 (PT1), 400 (PT2), and 800 (PT3) mg/kg Plotytarya strohilacea Sieb. et Zuce tannins for 42 days, respectively. The results showed that the average daily feed intake (ADFI) of the PT1 group was significantly lower than that of the control group, and there was a significant quadratic relationship between the ADFI and the concentration of tannin (P < 0.05). Compared with the control group, the F/G of broilers during the 22–42 days phase in the PT1 group showed a decreasing trend (P = 0.063). The serum catalase (CAT) activity in the PT1 group was significantly higher than those of the other three groups, and the effect was significantly quadratically related to the dosage (P < 0.05). The glutathione peroxidase (GSH-Px) activity in the PT1, PT2 and control groups were significantly higher than that of the PT3 group, and the effect was significantly quadratically related to the addition amount (P < 0.05). The serum total antioxidant capacity (T-AOC) activity in the PT1 group was significantly higher than that in the control group, and the effect was significantly quadratically related to the addition amount (P < 0.05). Compared to the control group, the villus height of jejunum in the PT1, PT2 and PT3 groups were significantly higher, and there was a significant quadratic relationship between the villus height of jejunum and the addition amount (P < 0.05). In addition, adding tannins to diets significantly increased Parabacteroides in the dominant genus (P < 0.05). In conclusion, dietary supplementation with Plotytarya strohilacea Sieb. et Zuce tannin improved the growth performance, antioxidant function, and intestinal morphology along with an increased abundance of Parabacteroides in the cecum, and the recommended dosage of tannin in broiler diets was 100 mg/kg.